SPANISH AND UKRAINIAN AS TWO LANGUAGES COMING FROM THE ONLY PROTO-INDO-EUROPEAN LINGUISTIC SOURCE: TYPOLOGICAL AND SOCIOLINGUISTIC APPROACHES - Korbozerova, Nina (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article examines the Spanish and Ukrainian languages in a comparative aspect. An attempt is made to consider these languages in terms of their origin and the possibility of multiple comparison. Is proposed a comprehensive research method based on the symbiosis of historical, typological, taxonomic, semantic and pragmatic approaches. In contemporary linguistics, there are a number of general linguistic techniques and methods for comparing linguistic structures. Today, linguists are expanding the scope of comparative research. Lately they resort to the discursive aspect, which makes it possible to carry out comparative linguistic analysis at the communicative, pragmatic, cognitive, linguo-cultural and linguo-ethnic levels. The comparative method verifies the value and continuous development of modern research of Ukrainian scientists in the field of linguistics, which, without a doubt, will contribute to the intensification of the process of learning foreign languages and the improvement of the training of translators highly rated. The use of the comparative taxonomic research method allows us to carry out an analysis of multiple aspects at any language level and find isomorphic nuances of the functional-semantic and structural level when comparing linguistic phenomena in two or more languages at both levels, whether synchronic or diachronic. Currently, genealogical, typological and territorial areas are considered the current areas of language systematization. Each of the directions is characterized by its own approaches, methods and criteria of discursive research. Thus, the genealogical approach involves taking into account historical factors, thanks to which it is possible to identify family links between the analyzed languages. The typological approach allows, in turn, to classify languages, according to linguistic type, according to the taxonomic criteria of structural kinship or non-kinship. Furthermore, linguistic typology deals with the study of type, universals, isomorphism and allomorphism in language. And finally, the territorial approach to the classification takes into account the principle of regional research, the aim of which is to study languages that have been in close contact for a long time and even under the influence of linguistic convergence. __________ References: • Familia indoeuropea, http://www.proel.org/index.php?pagina=mundo/indoeuro • https://lenguayliteraturasuperior.wordpress.com/2010/01/20/las-lenguas-del-mundo-y-de-europa/ • Verba, Curso de lexicología comparada (español-ucraniano). Vinnytsia: Nova Knyha, 2021. 232 p. • https://es.wikipedia.org/wiki/Lenguas_romances • https://www.inesem.es/revistadigital/idiomas/lenguas-indoeuropeas/